Income Diversification: A Way Towards Attracting Rural Youth in Agriculture (Indian Journal of Extension Education, 2022)
Attracting and retaining rural youth in agriculture (ARYA) is operational in different Krishi Vigyan Kendras (KVKs) in Bihar and Jharkhand. Six KVKs of Bihar (Aurangabad, Vaishali, East Champaran, West Champaran, Bhojpur and Bhagalpur), and four KVKs of Jharkhand (Ranchi, Chatra and Gumla East Singhbhum) were selected from 2017 and onwards for implementation of ARYA. Present investigation was done in 2020 and compared it with 2016-17 data i.e. before ARYA. The main aim of this project was to attract and involve unemployed rural youth in farming based enterprises. Results showed that among different enterprises, total 3687 number of rural youths trained out of them, 903 youths established their own enterprises and 700 youths run the enterprises sustainably. It has been concluded that poultry farming and nursery raising in Bihar and goat farming in Jharkhand attracted much more rural youth for its income generation.